1994
DOI: 10.1002/j.1460-2075.1994.tb06449.x
|View full text |Cite
|
Sign up to set email alerts
|

The mouse lethal nonagouti (a(x)) mutation deletes the S-adenosylhomocysteine hydrolase (Ahcy) gene.

Abstract: The lethal nonagouti (a(x)) mutation is a hypomorphic allele of the agouti coat color locus which, when homozygous, also leads to embryonic death around the time of implantation. To understand the molecular basis of these phenotypes, we identified and cloned a deletion breakpoint junction present in the ax chromosome. Long range restriction mapping demonstrated a simple deletion of approximately 100 kb, which does not affect agouti coding sequences, but begins only 4 kb 3′ of the last exon, and thus may affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 62 publications
4
66
0
Order By: Relevance
“…Although for patient 1 the disease was not closely monitored during the first months of life, it was reported that his psychomotor development was slow from the beginning, suggesting prenatal onset in this child too. In utero lethality of mice with a deletion that includes the AdoHcy gene is in accord with this impression (Miller et al 1994). Together, these findings suggest that myopathy might be a characteristic, probably congenital finding in AdoHcy hydrolase deficiency.…”
Section: Similarites Between Patients 1 Andsupporting
confidence: 55%
“…Although for patient 1 the disease was not closely monitored during the first months of life, it was reported that his psychomotor development was slow from the beginning, suggesting prenatal onset in this child too. In utero lethality of mice with a deletion that includes the AdoHcy gene is in accord with this impression (Miller et al 1994). Together, these findings suggest that myopathy might be a characteristic, probably congenital finding in AdoHcy hydrolase deficiency.…”
Section: Similarites Between Patients 1 Andsupporting
confidence: 55%
“…(16) Elevated homocysteine levels have been reported as a risk factor for dementia and Alzheimer's disease, (17) and as a possible risk marker for vascular disease. (18,19) Human AHCY deficiency, such as in hypermethionemia, results in severe biochemical abnormalities, including plasma elevations of 150-fold in SAH, 30-fold in SAM and 12-fold in methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, physiologically, SAHH not only serves to sustain the flux of methionine sulphur toward cysteine, but is also an essential enzyme playing a key role in the regulation of biological methylation (Cantoni and Chiang 1980;Hermes et al 2004). In vertebrates, SAHH is the only enzyme known to hydrolyse the SAH formed, and deletion of the SAHH gene is associated with embryo lethality in mice (Miller et al 1994). A recent study reported a proven human case of inherited SAHH deficiency in a Croatian patient (Baric et al 2004).…”
Section: Introductionmentioning
confidence: 99%